Graduates’ Necessities on English Education Curriculum of IAIN Parepare (A Need Analysis Study) - Syaiful A (Inspiring: English Education Journal, 2022)
This research aims to provide information about the graduates necessities on English education curriculum of IAIN Parepare. This research is descriptive study with a survey method. The population of this research is the graduates of English Education Program at IAIN Parepare. The total population of this study were 255 graduates. In this research, purposive sampling is used to determine the sample and the number of samples are 72 graduates which is done by the Slovin formula. This research used questionnaire in collecting the data and using percentage technique to see the frequency of the respondents’ answers. The result of this research shows that the graduates necessities on English education curriculum are courses that have a direct impact on their teaching abilities. Keywords: Curriculum, Need Analysis, Graduates Necessities